Development and Validation of a Normal Phase Chiral HPLC Method for Analysis of Afoxolaner Using a Chiralpak® AD-3 Column. (30th November 2016) - Zhuang, Jinyou; Kumar, Satish; Rustum, Abu
Abstract: Afoxolaner is a new antiparasitic molecule from the isoxazoline family that acts on the insect acarine gamma-aminobutyric acid and glutamate receptors. Isoxazoline family of compounds has been employed as active pharmaceutical ingredient in drug products prescribed for control of fleas and ticks in dogs. Afoxolaner with a chiral center at isoxazoline ring exists as a racemic mixture. A normal phase chiral high performance liquid chromatography analytical method has been developed to verify that afoxolaner is a racemic mixture as demonstrated by specific rotation, as well as to determine enantiomeric purity of single enantiomer samples. A Chiralpak ® AD-3 column (150 × 4.6 mm I.D.) maintained at 35°C was used in the method. Analytes were analyzed with an isocratic elution using n -Hexane/IPA/MeOH (89:10:1, v/v/v) as the mobile phase with a detection wavelength of 312 nm. Desired separation of the two enantiomers was achieved in <10 minutes with resolution and selectivity factors of 5.0 and 1.54, respectively. The analytical method was appropriately validated according to ICH guidelines for its intended use. ® All marks are the property of their respective owners.